2016
DOI: 10.1063/1.4952707
|View full text |Cite
|
Sign up to set email alerts
|

Surface and finite size effects impact on the phase diagrams, polar, and dielectric properties of (Sr,Bi)Ta2O9 ferroelectric nanoparticles

Abstract: In the framework of the thermodynamic approach Landau-Ginzburg-Devonshire (LGD) combined with the equations of electrostatics, we investigated the effect of polarization surface screening on finite size effects of the phase diagrams, polar and dielectric properties of ferroelectric nanoparticles of different shapes. We obtained and analyzed the analytical results for the dependences of the ferroelectric phase transition temperature, critical size, spontaneous polarization and thermodynamic coercive field on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…Such a research can be very useful for the science itself and for advanced applications, because the theory of size effects in nanoparticles allows us to determine the physical origin of polar and other anomalies in physical properties, the change in the temperature of a phase transition in nanoparticles with a decrease of their size. In particular, by using the phenomenological approach, Niepce [117], Huang et al [118,119], Ma [120], Eliseev et al [50], and Morozovska et al [11,[121][122][123][124] showed that the transition temperature variations and the enhancement or weakening of polar properties in spherical and cylindrical nanoparticles are governed by various physical mechanisms, such as the correlation effect, depolarization fields, flexolectricity, electrostriction, and surface tension.…”
Section: Multiferroic Nanoparticles the State Of Artmentioning
confidence: 99%
“…Such a research can be very useful for the science itself and for advanced applications, because the theory of size effects in nanoparticles allows us to determine the physical origin of polar and other anomalies in physical properties, the change in the temperature of a phase transition in nanoparticles with a decrease of their size. In particular, by using the phenomenological approach, Niepce [117], Huang et al [118,119], Ma [120], Eliseev et al [50], and Morozovska et al [11,[121][122][123][124] showed that the transition temperature variations and the enhancement or weakening of polar properties in spherical and cylindrical nanoparticles are governed by various physical mechanisms, such as the correlation effect, depolarization fields, flexolectricity, electrostriction, and surface tension.…”
Section: Multiferroic Nanoparticles the State Of Artmentioning
confidence: 99%
“…Such study may be very useful for science and advanced applications, because the theory of finite size effects in nanoparticles allows one to establish the physical origin of the polar and other physical properties anomalies, transition temperature and phase diagrams changes appeared with the nanoparticles sizes decrease. In particular, using the continual phenomenological approach Niepce [52], Huang et al [53,54], Ma [55], Eliseev et al [56] and Morozovska et al [57,58,59,60,61] have shown, that the changes of the transition temperatures, the enhancement or weakening of polar properties in spherical and cylindrical nanoparticles are conditioned by the various physical mechanisms, such as correlation effect, depolarization field, flexoelectricity, electrostriction, surface tension and Vegardtype chemical pressure.…”
Section: Multiferroelectric Nanoparticles State-of-artmentioning
confidence: 99%
“…Hence, donor doping of SBN within the limit of orthorhombic distortion (ba) and orthorhombicity ()ε=2ab()a+b greatly enhances its properties . The presence of foreign elements has an influence on the flexo‐chemical effect of the phase transition, polar and dielectric properties of these materials . In this sense, donor doping with W6+ and Mo6+ with higher valency but lower ionic radius than B‐site ion suppress the oxygen vacancy at the same time increase the rattling space within the octahedra .…”
Section: Introductionmentioning
confidence: 99%